Novel Technique for Reduction of Ankle Valgus Malunion and Chronic Talus Subluxation during Hindfoot Nailing - Matthew Ciminero; Kevin Kang; Amr Abdelgawad (Case Reports in Orthopedics)
In recent years, there has been a significant increase in the incidence and severity of ankle fractures in the elderly. We present a case of an elderly patient with significant medical comorbidities and social issues who sustained an unstable ankle fracture that led to a severe malunion secondary to refusal for surgery and noncompliance with weight-bearing precautions. By choosing an intramedullary fixation method that can be inserted through a biologically advantageous surgical exposure, we can permit early mobilization, create a stable plantigrade foot for ambulation, and alleviate the expected noncompliance with weight-bearing precautions in this patient. Despite debridement of callus, fibular osteotomy, and plate-assisted reduction, a displaced valgus angulation of the ankle joint remained. The nail was removed then reinserted backwards with the bend directed medially instead of its normal lateral position in order to use the bend in the nail as a reduction aid to finalize the reduction. We feel this technique may be of assistance to future surgeons encountering a similar situation.